Performance management in Ghana’s local government: a case study of Ada East District Assembly (Commonwealth Journal of Local Governance, 2020)
This article examines performance management in Ghana’s local governments through a case study of the on-the-ground experiences of staff at Ada East District Assembly, in the south-east of the country. The study found that performance management is envisaged in the preparation of action plans. However, the evidence also showed that severe logistical constraints, poor capacity resulting from inadequate training and poor supervision remain key challenges. In practice it was shown that performance management may achieve its intended results when accompanied by continuous employee performance evaluation.